2022
DOI: 10.21203/rs.3.rs-2009062/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emotion dysregulation as cross-disorder trait in child psychiatry predicting quality of life and required treatment duration

Abstract: Background Emotion dysregulation (ED) is increasingly under investigation as a cross-disorder trait, and is by some considered as the core feature in mental disorders. The underlying assumptions are that ED is a trait that manifests similarly across disorders and with similar impact. The aims of this study are to examine the shared and specific features of ED in relation to DSM-categories in a large sample of clinically referred youth. Methods Information on clinical diagnosis (Attention Deficit/Hyperactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Regarding the rate of ADHD comorbidity in autistic children, our figure (32.8%) is remarkably similar to the 29.5% referred in community samples by the meta‐analysis of Rong et al (2021), but lower than those found in clinical samples (40.4%–61.8%) (Casseus et al, 2023; Houghton et al, 2017; Rau et al, 2020; Rong et al, 2021). However, considering the age group, the 21.9% found in preschoolers was similar to the 20.4% rate shown by Fucà et al (2023) and the 17% by Bierens et al (2023) in Italian and Netherlands clinical samples, respectively. We found a significantly higher rate of autism and ADHD comorbidity in school‐aged children (46.2%) than in preschool‐age children (21.9%), differences also shown by Casseus et al (2023) (45.4% and 14.6%, respectively) but not obtained by other authors (Fucà et al, 2023; Houghton et al, 2017; Rong et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Regarding the rate of ADHD comorbidity in autistic children, our figure (32.8%) is remarkably similar to the 29.5% referred in community samples by the meta‐analysis of Rong et al (2021), but lower than those found in clinical samples (40.4%–61.8%) (Casseus et al, 2023; Houghton et al, 2017; Rau et al, 2020; Rong et al, 2021). However, considering the age group, the 21.9% found in preschoolers was similar to the 20.4% rate shown by Fucà et al (2023) and the 17% by Bierens et al (2023) in Italian and Netherlands clinical samples, respectively. We found a significantly higher rate of autism and ADHD comorbidity in school‐aged children (46.2%) than in preschool‐age children (21.9%), differences also shown by Casseus et al (2023) (45.4% and 14.6%, respectively) but not obtained by other authors (Fucà et al, 2023; Houghton et al, 2017; Rong et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…Also, without reaching significant differences probably due to the small size of this sample, the emotional DP showed a slightly higher score in the comorbid compared with the other clinical groups. Other authors have found that impaired emotional self‐regulation is more prevalent in youth with ADHD or/and autism (Bierens et al, 2023; Ventura et al, 2022) and that the shared association of these characteristics could predict social challenges (Jaisle et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation